Removal efficiency and pathways of phosphorus from wastewater in a modified constructed rapid infiltration system. (10th September 2020) - Su, Chengyuan; Zhu, Xiaowen; Shi, Xinwei; Xie, Ying; Fang, Yitao; Zhou, Xibing; Huang, Zhi; Lin, Xiangfeng; Chen, Menglin
Abstract: This study investigated the removal of phosphorus in a modified constructed rapid infiltration system (CRIS). The mechanism of phosphorus removal in the CRIS was studied from the perspective of enzymes, the microbial communities, and their metabolic functions. When the chemical oxygen demand (COD) concentration in the influent was increased from 550 to 650 mg/L to about 1100 mg/L, the total phosphorus (TP) removal efficiency increased, with an effluent TP concentration of about 0.16 mg/L in the CRIS. The matrix in the column contained iron and aluminium elements, which reacted with phosphate in the wastewater, resulting in phosphorus precipitation and, consequently, phosphorus removal. The maximum phosphine production was 1.73 and 0.24 mg/m 3 in the matrix and the column ventilator. The alkaline phosphatase activity which had a positive effect on the phosphorus removal was increased in the upper layer of the column. High-throughput sequencing analysis showed that the dominant bacterial phylum in the CRIS was Proteobacteria (49.33–51.8%). The abundance of Dechloromonas in the lower and upper layer of the column was 1.51 and 0.67%. The gene numbers of the phosphatidylinositol signaling system, the phosphonate and phosphinate metabolism, and the phosphotransferase system were 24, 468, 10, 661, and 20, 909 in the upper layer and 27, 408, 13, 476, and 31, 192 in the lower layer of the column. Graphical abstract: Image 1 Highlights: 90% of TP can be removed by the CRIS. PH3 plays a role in TP removal in the CRIS. Phosphonate metabolism and Phosphotransferase system were observed in the KEGG database.